Effects and mechanisms of action of sildenafil citrate in human chorionic arteries - Lynch Tadhg; O'Toole Daniel; Maharaj Chrisen H; Carney John; Jarman James; Higgins Brendan D; Morrison John J; Laffey John G (BMC, 2009)
Abstract Objectives Sildenafil citrate, a specific phosphodiesterase-5 inhibitor, is increasingly used for pulmonary hypertension in pregnancy. Sildenafil is also emerging as a potential candidate for the treatment of intra-uterine growth retardation and for premature labor. Its effects in the feto-placental circulation are not known. Our objectives were to determine whether phosphodiesterase-5 is present in the human feto-placental circulation, and to characterize the effects and mechanisms of action of sildenafil citrate in this circulation. Study Design Ex vivo human chorionic plate arterial rings were used in all experiments. The presence of phosphodiesterase-5 in the feto-placental circulation was determined by western blotting and immunohistochemical staining. In a subsequent series of pharmacologic studies, the effects of sildenafil citrate in pre-constricted chorionic plate arterial rings were determined. Additional studies examined the role of cGMP and nitric oxide in mediating the effects of sildenafil. Results Phosphodiesterase-5 mRNA and protein was demonstrated in human chorionic plate arteries. Immunohistochemistry demonstrated phosphodiesterase-5 within the arterial muscle layer. Sildenafil citrate produced dose dependent vasodilatation at concentrations at and greater than 10 nM. Both the direct cGMP inhibitor methylene blue and the cGMP-dependent protein kinase inhibitor Rp-8-Br-PET-cGMPS significantly attenuated the vasodilation produced by sildenafil citrate. Inhibition of NO production with L-NAME did not attenuate the vasodilator effects of sildenafil. In contrast, sildenafil citrate significantly enhanced the vasodilation produced by the NO donor sodium nitroprusside. Conclusion Phosphodiesterase-5 is present in the feto-placental circulation. Sildenafil citrate vasodilates the feto-placental circulation via a cGMP dependent mechanism involving increased responsiveness to NO.